LITERASI AGAMA DALAM MEMPERKUAT PENDIDIKAN MULTIKULTURALISME DI PERGURUAN TINGGI - Kadi, Titi (JURNAL ISLAM NUSANTARA, 2020)
This paper analyze the strengthening of religious literacy in strengthening multicultural education in higher education. This is motivated by the diversity in higher education, which is then feared that there will be divisions and acts of violence if multiculturalism education is not built or implemented, considering that students are individuals who are in the adolescent phase towards adulthood with changing emotional levels. This study uses a qualitative approach with library research, where the data analysis uses content analysis. The results showed that religious literacy in this case is a concept that not only means reading, but rather a deep understanding of religion so that it can become a basis for thinking and rationing on behavior. There are several things in strengthening religious literacy, including; 1) use and procurement of supporting media, 2) increase reading interest, 3) existence of student organizations, and 4) culture of discussion.